Slaughter of animals: poultry. (13th November 2019) - ,; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Depner, Klaus; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortázar Schmidt, Christian; Miranda Chueca, Miguel Ángel; Roberts, Helen Clare; et al.
Abstract: The killing of poultry for human consumption (slaughtering) can take place in a slaughterhouse or during on‐farm slaughter. The processes of slaughtering that were assessed, from the arrival of birds in containers until their death, were grouped into three main phases: pre‐stunning (including arrival, unloading of containers from the truck, lairage, handling/removing of birds from containers); stunning (including restraint); and bleeding (including bleeding following stunning and bleeding during slaughter without stunning). Stunning methods were grouped into three categories: electrical, controlled modified atmosphere and mechanical. In total, 35 hazards were identified and characterised, most of them related to stunning and bleeding. Staff were identified as the origin of 29 hazards, and 28 hazards were attributed to the lack of appropriate skill sets needed to perform tasks or to fatigue. Corrective and preventive measures were assessed: measures to correct hazards were identified for 11 hazards, with management shown to have a crucial role in prevention. Ten welfare consequences, the birds can be exposed to during slaughter, were identified: consciousness, heat stress, cold stress, prolonged thirst, prolonged hunger, restriction of movements, pain, fear, distress and respiratory distress. Welfare consequences and relevant animal‐based measures were described. Outcome tables linking hazards, welfare consequences, animal‐based measures, origins, and preventive and corrective measures were developed for each process. Mitigation measures to minimise welfare consequences were also proposed.